2014
DOI: 10.1002/adfm.201403108
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/Nanocrystal Hybrid Solar Cells: Influence of Molecular Precursor Design on Film Nanomorphology, Charge Generation and Device Performance

Abstract: In this work, molecular tuning of metal xanthate precursors is shown to have a marked effect on the heterojunction morphology of hybrid poly(3-hexylthiophene-2,5-diyl) (P3HT)/CdS blends and, as a result, the photochemical processes and overall performance of in situ fabricated hybrid solar cells. A series of cadmium xanthate complexes is synthesized for use as in situ precursors to cadmium sulfide nanoparticles in hybrid P3HT/CdS solar cells. The formation of CdS domains is studied by simultaneous GIWAXS (graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…The observed changes in film morphology may be derived from several factors such as the different primary crystallite sizes (28 nm for NiXa-C6, 22 nm for NiXa-C7), differences in crystallization behavior of the precursors during deposition of the precursor films or different precursor reactivities, which have important implications on nucleation and growth kinetics. Regarding this latter issue, MacLachlan et al [53] and Lewis et al [60] have already demonstrated that the morphology of metal sulfide nanocomposites can be efficiently tuned by the chemical structure of xanthate or dithiocarbamate complexes. Similar as in the work of Lewis et al, the observed differences in film morphology in this study might also originate from changes in precursor reactivity.…”
Section: Preparation Of Nickel Sulfide Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed changes in film morphology may be derived from several factors such as the different primary crystallite sizes (28 nm for NiXa-C6, 22 nm for NiXa-C7), differences in crystallization behavior of the precursors during deposition of the precursor films or different precursor reactivities, which have important implications on nucleation and growth kinetics. Regarding this latter issue, MacLachlan et al [53] and Lewis et al [60] have already demonstrated that the morphology of metal sulfide nanocomposites can be efficiently tuned by the chemical structure of xanthate or dithiocarbamate complexes. Similar as in the work of Lewis et al, the observed differences in film morphology in this study might also originate from changes in precursor reactivity.…”
Section: Preparation Of Nickel Sulfide Thin Filmsmentioning
confidence: 99%
“…The attractive properties of metal xanthates, like their usually good stability (also in solution), relatively low decomposition temperature (below 200°C) and simplicity to tailor solubility and decomposition behavior by variation of their organic side chains, have ensured that they are widely employed in the preparation of various metal sulfide nanomaterials [35][36][37][38][39][51][52][53][54][55][56][57][58][59][60].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…roll-toroll manufacturing. 16,17,30 To date, the only metal sulphides to have been synthesised by the decomposition of single source precursors in a polymer film are CdS, 4,5,32,33 , CuInS 2 , 29 ZnS, 34,35 Bi 2 S 3 , 36 and Sb 2 S 3 . 31 Despite an extensive family of single source precursor molecules used for chemical vapour deposition and nanoparticle synthesis, [37][38][39][40][41][42] relatively few have been investigated within a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the chemical surrounding of Ag NPs that was affected by the addition of the Fe NPs, which in turn resulted in change in shape, size, and electron density of the NPs [39]. The shift could also be attributed to the extended defects and the microstrains of the peak shapes and widths of the NPs since NPs with the diameter less 100 nm are known to have defects on their surface [40].…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%